The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4314/ejb.v16i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant-growth-promoting rhizobacteria inoculation on plant growth, productivity and economics of Basmati rice

Abstract: A field experiment was conducted in a wet season (Kharif) to study the effects of plant growthpromoting rhizobacteria(PGPR) inoculation on agronomic traits and productivity of Basmati rice (cv. 'Pusa Basmati 1401') in a randomized block with twelve treatments. We evaluated one bacterial (Providencia sp. PW5) and one cyanobacterial strain (Anabaena sp. CR3), and also a Multani mitti (Fuller's earth)-based blue-green algal biofertilizer (a composite culture of Anabaena, Nostoc, Tolypothrix and Aulosira sp.). Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The balanced and adequate nutrient supply favoured better crop growth which ultimately increased the yield. Similar findings were reported by Singh et al (2008) and Meena et al (2014). Harvest index (HI) was significantly influenced by planting methods but nutrient management options had no significant effect on HI.…”
Section: Growth and Yield Of Ricesupporting
confidence: 80%
“…The balanced and adequate nutrient supply favoured better crop growth which ultimately increased the yield. Similar findings were reported by Singh et al (2008) and Meena et al (2014). Harvest index (HI) was significantly influenced by planting methods but nutrient management options had no significant effect on HI.…”
Section: Growth and Yield Of Ricesupporting
confidence: 80%
“…11,17,2 Better nutrition ultimately leads to luxurious root growth to extract nutrients and moisture more efficiency from deeper soil layer resulting better growth and development of plants, more leaf area and greater dry matter accumulation. 12,3,21 22,30,9,1 Interaction effect of variety and phosphorus levels was found significant with respect to shelling percent and 100-kernel weight (Table 3). In Kormaki variety maximum 100-kernel weight was recorded with 60 kg P2O5 ha -1 , whereas, greatest 100kernel weight of Paparri variety was found with 80 kg P2O5 ha -1 .…”
Section: Resultsmentioning
confidence: 93%
“…The groundnut protein consists of two type's proteins, namely, arachin and conarachin. 26 Amino Acid analysis shown that the main amino acid was glutamic acid (22)(23)(24)(25)(26)(27) %, arginine (11-13%), aspartic acid (8-13%). 15 Groundnut is cultivated worldwide in tropical, subtropical and warm temperature regions between 40⁰ N and 40⁰ S latitude.…”
Section: Introductionmentioning
confidence: 99%
“…Despite being most abundantly available element in atmosphere (* 78% by volume), nitrogen (N) continues to be the most growth limiting nutrient element and need to be given prime attention for better crop production [2,48]. The atmospheric N 2 cannot be taken up by plants unless it has been converted into plant utilizable forms either biologically by a process called biological N 2 fixation or artificially in the forms of chemical fertilizers.…”
Section: Nitrogen Fixationmentioning
confidence: 99%
“…Adesemoye et al [2] reported that, with the application of PGPR and mycorrhizal fungi, the recommended dose of fertilizer could be reduced up to 70% without significant reduction in tomato yield. Meena et al [48] observed that the application of PGPR consortia (consisting of bacterial and cyanobacterial inoculations and compost) and 2/3 rd of the recommended dose of N (* 80 kg/ha) led to significant increase in rice grain yield by 90% and 4.5% compared with no N and full dose of N application, respectively. Rice inoculated with PGPR showed stimulation effect on nitrogenase enzyme and hence induced N fixation by blue-green algae [73].…”
Section: Nitrogen Fixationmentioning
confidence: 99%